Typology of media use and its associations with parent and child factors among elementary school children: a latent profile analysis - Yangmi Lim (BMC Psychology)
Abstract Background Media use literature has predominantly adopted a variable-centered approach. However, a limitation of this approach is that it overlooks the nuanced differences between individual participants or groups in media use types. To address this limitation, this study adopts a person-centered approach to identify media use types among third-grade elementary school children based on the time spent on media and purposes. Additionally, the study examined the associations between the media use types and parent and child factors. Methods Data were collected from 1,327 third-grade children (49.7% girls) in South Korean elementary schools and their parents, who participated in the Panel Study on Korean Children conducted by the Korea Institute of Child Care and Education. A latent profile analysis was performed. Results This study identified three media use profiles in children: Learning-oriented/shortest-use time (primarily using media for learning purpose and for the shortest duration; 54.2%), Multipurpose-oriented/long-use time (using media for multiple purposes and for a long duration; 22.5%), and Games & entertainment-oriented/longest-use time (primarily using media for games and entertainment purposes and for the longest duration; 23.3%). Children’s gender and permissive parenting styles influenced the membership of specific media use profiles. Boys were more likely than girls to belong to the Games & entertainment-oriented/longest-use time profile, whereas girls were more likely than boys to belong to the Multipurpose-oriented/long-use time profile. In addition, higher levels of mothers’ permissive parenting styles were associated with an increased likelihood of belonging to the Games & entertainment-oriented/longest-use time profile rather than the Learning-oriented/shortest-use time profile. Overall, the members of the Games & entertainment-oriented/longest-use time profile exhibited the highest levels of problematic media use, executive function difficulties (planning–organizing, behavioral control, and attention–concentration difficulties), and externalizing and internalizing problems. Conclusions Based on the research findings, this study recommends intervention strategies for parents (especially mothers) and schools to effectively monitor children’s media use and facilitate their healthy media use by considering differential media use types according to children’s gender.